2015
DOI: 10.1007/s10916-015-0224-4
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Online Health Education: Perception from Consumers and Health Professionals

Abstract: With the advancement in technology and availability of the Internet, online health education could become one of the media for health education. As health education is to persuade patients on health behavioural change, understanding perceived benefits of online health education is an important aspect to explore. The aim of this study is to explore consumers and health professionals opinion on online health education. Literature review was conducted and identified the benefits of online health education (OHE). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 48 publications
1
49
0
7
Order By: Relevance
“…Effectiveness of the Internet in modification of consumer behaviour has also been reported in previous studies [5,[8][9][10][11]. Advances in mobile technology may provide some solutions to global health issues caused by physical inactivity.…”
Section: Introductionsupporting
confidence: 60%
“…Effectiveness of the Internet in modification of consumer behaviour has also been reported in previous studies [5,[8][9][10][11]. Advances in mobile technology may provide some solutions to global health issues caused by physical inactivity.…”
Section: Introductionsupporting
confidence: 60%
“…Several studies found that OPE offered better health education and improved disease-related knowledge amongst patients [8,1].…”
Section: Benefits Of Online Patient Educationmentioning
confidence: 99%
“…OPE can also improve a patient's emotional state and satisfaction [1]. Patients utilising OPE in conjunction with clinical consultations will ultimately save more time than those who seek information solely from their physicians.…”
Section: Benefits Of Online Patient Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that supports the contention that online health information provision, education and management support can benefit health consumers [5]. Several medication management applications have been developed to assist consumers with their medication management and monitoring.…”
Section: Introductionmentioning
confidence: 99%